The use of granulated modified zeolite Y for the removal of arsenic and selenium species - 389575 Noor Hidayah Idris; Alias Mohd. Yusof (Skudai : Universiti Teknologi Malaysia, 2008)
Project Paper (Sarjana Muda Sains (Kimia Industri)) - Universiti Teknologi Malaysia, 2008